PERBEDAAN PENGARUH METODE LATIHAN BERBEBAN LINIER DAN NON LINIER TERHADAP PENINGKATAN POWER OTOT LENGAN DITINJAU DARI KEKUATAN OTOT LENGAN. - BAGUS KUNCORO (Universitas Tunas Pembangunan, 2012)
This research was aimed at knowing: 1) The effect difference of linier and non linier weight training on the arm muscle power, 2) The effect difference on the arm muscle power between the students having higher strength of arm muscle and the lower ones, 3) Interaction between the training method and strenght on the arm muscle power. The applied method in this research was an experimental method using 2 x 2 factorial designs. The population of this research was the male students of Sport Extracuricular of SMP Negeri I Tulung, Klaten in Academic Year of 2009/2010) as many as 50 students. The sample of the research is 40 students taken using purposive Random Sampling. The variable of the research consists of three variables: independent is training method (linier and non linier weight training), attributive is strengthness of arm muscle, and dependent variable is arm muscle power. Entire needed data in this research was obtained through test and measurement on the arm muscle strength using arm dynamometer as well as the muscle power one using medicine ball test. The technique of analyzing data in this research is two-way Varian Analysis (ANAVA) followed by the Newman-Keul’s interval test at significance level of α = 0.05. The result shows that 1) There is significant effect difference of linier and non linier weight training on arm muscle power. 2) There is significant difference of arm muscle power between the students having higher strength and lower ones. 3) There is a significant interaction between the training method and the muscle strength level with on the result of arm muscle power. The group of eleventh male students having higher strength of arm muscle is more suitable to be coached using the linier weight training, while the group of students having lower strength of arm muscle is better to be coached using non linier weight training.